Russia's energy relations in Southeastern Europe: an analysis of motives in Bulgaria and Greece. Issue 5 (3rd September 2017) - Jirušek, Martin; Vlček, Tomáš; Henderson, James
Abstract: Although officially Russian state-owned energy companies operate as independent entities, their actions often lead to suspicion that they are acting as a tool of Russian state foreign policy. Countries on the southeastern borders of Europe – Bulgaria and Greece – are prime examples of where this might be the case, since they not only have a central position in Russia's plans to penetrate European markets through new transport infrastructure but are also part of competing plans for routing non-Russian gas to Western markets. The main focus of the present research is on the natural gas and oil sectors, as these are the traditional foundation of Russian energy exports to Europe. The aim of this paper is thus to provide an objective, evidence-based analysis of Russian activities in the natural gas and oil sectors of Greece and Bulgaria in order to establish whether its actions have been implicitly or explicitly politicized and have served to strengthen Russian influence in the region.